Juvenile idiopathic arthritis outcome and prognosis according to catamnesis evaluation - O V Semenova; S O Salugina (Научно-практическая ревматология, 2005)
Objective. To study outcome and prognosis in pts with juvenile idiopathic arthritis (JIA). Material and methods. 239 JIA pts with disease duration of 10 years and more were analyzed. 80 children and adolescents before 18 years old (66 girls and 14 boys) were included in group 1. Arthritis clinical and laboratory activity, radiological stage and functional status according to Steinbroker and CHAQ questionnaire were assessed. 159 grown up pts (109 female and 50 male) suffering from JIA from childhood were included in group 2. They were examined using Stanford Health Assessment Questionnaire (HAQ) and a specially developed social status questionnaire. Results. Half pts of group 1 had recurrence of the disease during examination but activity in most cases did not exceed stage I or 2 (54% and 31% respectively). Joint destructive changes were revealed in 50% of pts. 80% of pts had radiological signs of secondary osteoarthritis. Amyloidosis was revealed in 2 from 27 pts with systemic type of JIA. 68% of pts had 1 or 2 functional class. 1/3 of pts did not have functional limitations (CHAQ=0). 13% of pts had maximal disability with CHAQ ranging from 2,1 to 3,0 (pts with polyarticular and systemic types of JIA. Most grown up pts (59%) considered their health as good. Substantial part of them worked or learned. 10 pts did not worked because of the disease (1,5%). 61% of pts did not have functional limitations (HAQ=0). 32% of pts were disabled. Most of them had 3 or 2 disability degree and had possibility to work. Conclusion. Substantial part of pts with longstanding JIA have stabilization of the disease or remission. Recurrent course of the disease was characterized by decrease of activity. Most children and grown ups with longstanding disease have relatively benign functional outcome. Pts with polyarticular and systemic types of JIA require especial attention because they have maximal risk of joint destruction with severe disability.